2010
DOI: 10.1007/s00181-010-0403-6
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index in families: spousal correlation, endogeneity, and intergenerational transmission

Abstract: Body mass index, Endogeneity, Familial correlation, I10, I12,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…This relationship is much stronger when we restrict the sample to mothers with morbid obesity, where the percentage‐point difference in the probability of being an adolescent with obesity is estimated to be 0.144. In addition, we estimate that the intergenerational elasticity of the BMI between mother and adolescent is 0.242, which is consistent with estimates from other countries (Whitaker et al , ; Abrevaya & Tang, ; Murrin et al , ; Dolton & Xiao, , ). When we account for adolescent‐specific fixed effects, the estimated elasticity reduces to 0.043.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…This relationship is much stronger when we restrict the sample to mothers with morbid obesity, where the percentage‐point difference in the probability of being an adolescent with obesity is estimated to be 0.144. In addition, we estimate that the intergenerational elasticity of the BMI between mother and adolescent is 0.242, which is consistent with estimates from other countries (Whitaker et al , ; Abrevaya & Tang, ; Murrin et al , ; Dolton & Xiao, , ). When we account for adolescent‐specific fixed effects, the estimated elasticity reduces to 0.043.…”
Section: Introductionsupporting
confidence: 90%
“…Our most extensive model returns an intergenerational elasticity estimate of 0.242, with a standard error of 0.017. Murrin et al () estimated 0.20 for Ireland, Whitaker et al () estimated 0.27 for England, Dolton and Xiao () estimated 0.141 for China, and Abrevaya and Tang () estimated a range between 0.22 and 0.25 for the USA. More recent work by Dolton and Xiao () showed a range of estimates between 0.117 in Mexico to 0.215 in China, with elasticity estimates for Indonesia, the UK (two different cohorts), the USA and Spain falling in between.…”
Section: Discussionmentioning
confidence: 99%
“…The parents’ BMI are expected to be highly correlated, but no multicollinearity diagnostic was performed to investigate and discuss the potential impact of multicollinearity in the instability of the estimated coefficients when BMIs from both parents were kept in the regression model. Numerous studies [18–22] have shown that BMIs of spouses are correlated possibly due to the shared environment and the change in the coefficient estimate may be due to collinearity between the BMIs of spouses. Similarly, Desai et al [23] investigated independent effects of selected variables on diastolic dysfunction as an outcome variable, defined as severe-diastolic dysfunction versus normal diastolic function, using polytomous logistic regression analysis [23].…”
Section: Introductionmentioning
confidence: 99%
“…13 Essa abordagem que obedece a um padrão empírico e específico para cada idade e 12 O cálculo desse indicador é dado por: IMC = peso/(altura 2 ) , com o peso expresso em quilograma (kg) e a altura em metro (m). 13 Abrevaya & Tang (2010) realçam que as condições nutricionais das crianças são determinadas primariamente por fatores genéti-cos e pelo ambiente comum (hábitos saudáveis, questões locacionais, peer-effects, entre outros). No entanto, para eles a taxa de crescimento de indivíduos com excesso de peso nos últimos anos indica que o fator ambiente comum vem assumindo um maior grau de importância.…”
Section: Indicadores De Exposição Aos Fatores De Risco Comportamentaisunclassified